Solving North Korean missile crisis - Demczuk, Andrzej (Asia in World Politics: Past, Present, and Future, 2021)
The Article examines the North Korean missile crisis situation. It starts with providing a background of North Korean nuclear program and identifying primary drivers of North Korea’s continued interest in weapons of mass destruction. The article analyses hypothetical solutions like military action and the ineffectiveness of the economic sanctions. The three solutions to North Korean case start with a plan to prepare a policy of regime transition, and are followed with an explanation why making Pyongyang feel more secure and helping to improve its country economy are crucial to achieving American goal, which is at least freezing its country nuclear weapons program.